Compact and tunable active-plasma lens system for witness extraction and driver removal. (July 2020) - Dotto, A. Del; Chiadroni, E.; Cianchi, A.; Faillace, L.; Ferrario, M.; Iovine, P.; Masullo, M.R.; Pompili, R.
Abstract: Plasma based technology will allow an unprecedented reduction of the size of accelerating machines. Both fundamental research and applied science and technology will take profit of this feature. The same compactness is required downstream the accelerator module, where the plasma-accelerated beams usually experience a large angular divergences growth. Therefore compact, strong and tunable focusing devices are needed. Active-plasma lenses have been demonstrated to be a compact and affordable tool to generate radially symmetric magnetic fields. We present a new scheme using active-plasma lenses and a metallic collimator to catch and transport the witness bunch while removing the driver. The considered case study is in the context of the EuPRAXIA project.